Ethnopharmacology, Biological Evaluation, and Chemical Composition of Ziziphus spina-christi (L.) Desf.: A Review - Mahmoud Dogara Abdulrahman; Ali Muhammad Zakariya; Harmand A. Hama; Saber W. Hamad; Sawsan S. Al-Rawi; Sarwan W. Bradosty; Ahmad H. Ibrahim (Hindawi Limited, 2022)
Medicinal plants are the primary raw materials used in the production of medicinal products all over the world. As a result, more study on plants with therapeutic potential is required. The tropical tree Ziziphus spina belongs to the Rhamnaceae family. Biological reports and traditional applications including management of diabetes and treatment of malaria, digestive issues, typhoid, liver complaints, weakness, skin infections, urinary disorders, obesity, diarrhoea, and sleeplessness have all been treated with different parts of Z. spina all over the globe. The plant is identified as a rich source of diverse chemical compounds. This study is a comprehensive yet detailed review of Z. spina based on major findings from around the world regarding ethnopharmacology, biological evaluation, and chemical composition. Scopus, Web of Science, BioMed Central, ScienceDirect, PubMed, Springer Link, and Google Scholar were searched to find published articles. From the 186 research articles reviewed, we revealed the leaf extract to be significant against free radicals, microbes, parasites, inflammation-related cases, obesity, and cancer. Chemically, polyphenols/flavonoids were the most reported compounds with a composition of 66 compounds out of the total 193 compounds reported from different parts of the plant. However, the safety and efficacy of Z. spina have not been wholly assessed in humans, and further well-designed clinical trials are needed to corroborate preclinical findings. The mechanism of action of the leaf extract should be examined. The standard dose and safety of the leaf should be established.